Strategi Pemasaran Syariah Dalam Mempertahankan Eksistensi Lembaga Keuangan Syariah Ditengah Pandemi Covid-19 - Afifuddin, M. (Sekolah Tinggi Agama Islam Ma`arif Kalirejo Lampung Tengah, 2023)
In the midst of the economic crisis that hit Indonesia and even the whole world due to the Covid-19 pandemic and the current tight competition of sharia institutions, one of which is sharia cooperatives that continue to strive to maintain their existence in society through the attention of members and always provide excellent service to members, marketing (marketing) is one of the methods used to attract members. This research is a field research. In accordance with the title that the researcher adopted, this research uses a qualitative approach. While the data analysis using the inductive method. The technique used to determine the validity of the data in this study are: Triangulation. Based on the results of the discussion, it can be concluded that the Islamic marketing strategy in maintaining the existence of Islamic financial institutions in the midst of the Covid-19 pandemic is by implementing sharia marketing strategies, public relations strategies, communication strategies, and producer creative strategies. The sharia marketing strategy can maintain existence in the midst of the Covid-19 pandemic, this is evident from the addition of the number of new members during the Covid-19 pandemic. The implementation of an optimal strategy can be used as an effort to increase the number of customers, so that the company's assets will increase and can maintain the existence of Islamic financial institutions.